The utility of N,N-biotinyl glutathione disulfide in the study of protein S-glutathiolation. - Brennan, J; Miller, J; Fuller, W; Wait, R; Begum, S; Dunn, M; Eaton, P (2006)
Glutathione disulfide (GSSG) accumulates in cells under an increased oxidant load, which occurs during neurohormonal or metabolic stimulation as well as in many disease states. Elevated GSSG promotes protein S-glutathiolation, a reversible post-translational modification, which can directly alter or regulate protein function. We developed novel strategies for the study of protein S-glutathiolation that involved the simple synthesis of N,N-biotinyl glutathione disulfide (biotin-GSSG). Biotin-GSSG treatment of cells mimics a defined component of oxidative stress, namely a shift in the glutathione redox couple to the oxidized disulfide state. This induces widespread protein S-glutathiolation, which was detected on non-reducing Western blots probed with streptavidin-horseradish peroxidase and imaged using confocal fluorescence microscopy and ExtrAvidin-FITC. S-Glutathiolated proteins were purified using streptavidin-agarose and identified using proteomic methods. We conclude that biotin-GSSG is a useful tool in the investigation of protein S-glutathiolation and offers significant advantages over conventional methods or antibody-based strategies. These novel approaches may find widespread utility in the study of disease or redox signaling models where GSSG accumulation occurs.